CHANGES MEANING IN SWEAR WORDS - Damanik, Bernieke Anggita Ristia Damanik; Josua Silalahi (Sindoro: Cendikia Pendidikan, 2025)
Swear words have significantly evolved in modern society, shifting from their traditional role as offensive or taboo language to becoming dynamic tools in communication. This study explores the transformation of profanity, focusing on its meanings, functions, and usage. It examines how swear words have taken on new purposes, such as adding humor, emphasizing speech, expressing solidarity, and conveying identity. Using linguistic, cultural, and psychological perspectives, the research analyzes the influence of media, technology, and globalization in normalizing and reshaping profanity. Social media and popular culture have played a crucial role in spreading swear words across different cultures, resulting in varied interpretations and uses. The study also highlights generational differences, showing how younger people redefine and incorporate profanity to challenge norms, strengthen social connections, or assert individuality. Additionally, it investigates the decreasing shock value of swear words and their increasing presence in everyday language. By analyzing examples from music, movies, and online platforms, the research illustrates how language adapts to reflect societal and cultural shifts. The findings suggest that the evolving role of profanity reflects broader changes in communication styles, cultural trends, and social values, providing new insights into the continuous development of language.